1992
DOI: 10.3181/00379727-200-43456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Reduction in Sodium Intake on Cold-Induced Elevation of Blood Pressure in the Rat

Abstract: Chronic exposure of rats to cold (5 degrees C) induces hypertension within 3 weeks. The objective of this study was to determine the effect of treatment with graded levels of dietary NaCl on the induction of hypertension during chronic exposure to cold. Four groups of male rats were used. The first, given a commercial sodium-deficient diet containing 0.30% NaCl, served as the warm-adapted control group. The second, third, and fourth groups were given the same diet containing 0.075%, 0.15%, and 0.30% NaCl, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…Many studies about hypertension have been performed [8][9][10][11][12][13][14][15][16] in laboratory animals, but studies about hypertension in cold-exposed workers are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies about hypertension have been performed [8][9][10][11][12][13][14][15][16] in laboratory animals, but studies about hypertension in cold-exposed workers are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, plasma renin activity (PRA) is increased during exposure to cold and abolishment of the rise in PRA by renal denervation prevents the development of CIH [32] . Cold-exposed rats had an elevation of blood pressure that was proportional to the concentration of NaCl in the diet [49] , suggesting that CIH is sodium-dependent hypertension.…”
Section: The Major Animal Models Of Hypertensionmentioning
confidence: 99%
“…We have shown that continuous exposure to the cold causes cardiac hypertrophy, the left ventricle mass index was increased by 16% in CCE group. The cold induced hypertrophy of the myocardium has been demonstrated by other authors (Hamilton and Ferguson 1972;Harri et al 1984;van Bergen et al 1992). Apparently this hypertrophy in the heart is the result of an increase in blood pressure.…”
Section: Discussionmentioning
confidence: 63%
“…The first protocol (protocol 1) included animals with continuous cold exposures (CCE), they resided inside the refrigerator chamber (23 m 3 ) at +4°C two rats in a cage for four weeks (Kvetnansky et al 2012). The second protocol (protocol 2) included rats with long intermittent cold exposures (LICE) which were exposed at +4°C for 8 h daily for 4 weeks (van Bergen et al 1992). The third protocol (protocol 3) included animals which were subjected to brief intermittent cold exposures (BICE), which were in a cold chamber at +4°C for 1.5 h daily for 28 days (4 weeks) (Bozhko and Gorodetskaya 1994).…”
Section: Animals and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation